2014
DOI: 10.1016/j.juro.2013.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Readmission following Outpatient Urological Surgery

Abstract: Readmission after outpatient urological surgery occurs at a rate of 3.7%. A history of cancer, bleeding disorder, male gender, ASA level 3 or 4 and age were associated with readmission along with greater rates of medical and surgical complications. Our results may help guide risk reduction initiatives and prevent costly readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 21 publications
4
51
0
5
Order By: Relevance
“…In our analysis, only the ASA score was independently associated (p < 0.01) with hospitalization with 44% of patients with ASA score III who have been admitted to inpatient ward. The results of our study seem to be similar to those observed by Rambachan et al [21]. A multiinstitutional multivariate analysis of patient factors that contribute to readmission after outpatient urological surgery showed that cancer history, bleeding disorders, and ASA score III-IV were significant predictors of readmission.…”
Section: Discussionsupporting
confidence: 91%
“…In our analysis, only the ASA score was independently associated (p < 0.01) with hospitalization with 44% of patients with ASA score III who have been admitted to inpatient ward. The results of our study seem to be similar to those observed by Rambachan et al [21]. A multiinstitutional multivariate analysis of patient factors that contribute to readmission after outpatient urological surgery showed that cancer history, bleeding disorders, and ASA score III-IV were significant predictors of readmission.…”
Section: Discussionsupporting
confidence: 91%
“…Past research on the association between smoking status and readmission rates has produced equivocal results. [26][27][28][29][30][31][32][33][34] Many studies have examined commonly collected demographic variables. It has been reported that increasing age could potentially serve as a predictor of all-cause hospital readmissions, especially in patients over the age of 65.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the literature have investigated the reasons for re-admissions and the financial impact of readmissions (4,5). The evaluation of these factors in the prediction and prevention of re-admissions can undoubtedly make a significant contribution.…”
Section: Discussionmentioning
confidence: 99%